Jack Kerouac's Duluoz legend : the mythic form of an autobiographical fiction - Jones, James T., 1948- (Southern Illinois University Press, 1999)
"In the only critical examination of all of Jack Kerouac's published prose, James T. Jones turns to Freud to show how the great Beat writer used the Oedipus myth to shape not only his individual works but also the entire body of his writing."--BOOK JACKET. "Like Balzac, Jones explains, Kerouac conceived an overall plan for his total writing corpus, which he called the Duluoz Legend after Jack Duluoz, his fictional alter ego. While Kerouac's work attracts biographical treatment - the ninth full-length biography was published in 1998 - Jones takes a Freudian approach to focus on the form of the work. Noting that even casual readers recognize family relationships as the basis for Kerouac's autobiographical prose, Jones discusses these relationships in terms of Freud's notion of the Oedipus complex."--Jacket